Employees and the great recession - Bardwick, Judith M. (Henry Stewart Talks, 2014)
Whole industry disappeared, Success and no competition caused complacency, When Japanese cars first landed, Financial security disappeared, Economic growth slower than workforce growth, The great recession and the American dream, Job reduction, How is a recession defined?, The psychological recession, Strong feelings directly impact people's choices, Achieve commitment and engagement, Treat your people well and they’ll return the favor, Economic and psychological recessions will end, Success is the ultimate motivator